ANALYSIS OF CONSTRUSTION BUDGET FORMULATION : CASE STUDY PUBLIC WORK AGENCY OF TASIKMALAYA REGENCY GOVERNMENT - Kharisma, Bayu; Noor, Andar Mochamad Zamzam (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
Budget formulation as the first dimensions of budget cycle, has an important role to maintain. A lot of issues will be grow up related to budget priority, objectives, outcomes, and regulation as long as formulation expenditure policy in allocating recources. The study purpose is to explain about the steps in making project cost estimation especially on the stages of budget formulation at the executive budget process. There is a formulation of construstion cost compenent which is regulated by Public Work Minister Rule No.45/PRT/M/2007. Case study of two construction projects budget in Public Work Agency of Tasikmalaya Regency generate some result that the the early estimation cost of proposal in RKA/DIPA is acceptable regarding to its construction cost, but others have to be revised, related to  planning cost, supervision cost, and management cost.